GOVERNMENT SIZE AND FINANCIAL RATIOS ON FINANCIAL DISTRESS AND DISTRICT OR CITY GOVERNMENTS IN SOUTH SUMATERA PROVINCE - Marshanda Putri, Anggia; Ferina, Ika Sasti; Susanto, Hendra (Catholic University Musi Charitas, 2025)
Purpose This study aims to analyze the effect of government size and financial ratios on financial distress in district/city governments in South Sumatra Province. The variables used in this study include government size, regional financial independence, effectiveness ratio, and efficiency ratio. Design/Methodology/Approach This research employs a quantitative method with a descriptive and associative approach. The data used are secondary data obtained from local government financial reports for the period 2019-2023. The data analysis technique applied is multiple linear regression to examine the influence of each independent variable on financial distress. Findings The results indicate that government size has a significant impact on financial distress. Larger local governments tend to face more complex financial management challenges, which may increase the risk of financial distress if not accompanied by proper budget management.Additionally, regional financial independence is found to have a negative effect on financial distress, meaning that the higher the level of financial independence, the lower the likelihood of experiencing financial distress. The effectiveness and efficiency ratios also play a crucial role in determining local financial stability, where higher effectiveness in revenue realization and efficiency in budget utilization can help reduce financial distress risks. Practical Implications The findings of this study imply that local governments should focus more on managing finances efficiently and effectively. Larger governments must enhance their managerial capacity in budget management to minimize the risk of financial distress. Moreover, increasing financial independence by optimizing locally generated revenue (Pendapatan Asli Daerah - PAD) can serve as a strategy to reduce dependence on central government transfers and improve local financial stability. Originality/Value This study contributes to the literature on financial distress in local governments, particularly in Indonesia, by focusing on the under-researched context of district and city governments in South Sumatra Province. Unlike previous studies that often examine national or provincial level data, this research provides a localized analysis that captures the unique fiscal dynamics at the regional level. Moreover, the integration of government size along with financial ratios such as regional financial independence, effectiveness, and efficiency in a single model offers a more comprehensive framework for understanding financial distress. This approach provides practical insights for regional policymakers aiming to strengthen local fiscal resilience.